Spatial distribution of coffees from Minas Gerais state and their relation with quality - Neves Barbosa, Juliana; Meira Borém, Flávio; Ramos Alves, Helena Maria; Marin Lordelo Volpato, Margarete; Grossi Chquiloff Vieira, Tatiana; Oliveira de Souza, Vanessa Cristina (Coffee Science - ISSN 1984-3909, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>Coffee is the second most important agricultural exportation product in Brazil, constituting one of the main income sources of the Brazilian economy. The state of Minas Gerais is the country’s biggest coffee producer. Recently, coffees produced in the state have won national specialty coffee contests, which has increased their commercial value and established them in the market. Due to the necessity of more information on areas with potential for producing quality arabic coffees (Coffea arabica L.), the objective of this work was to relate the coffees entered in the Quality Contest-Coffees from Minas Gerais, in 2007 and 2008, with the environmental characteristics of the state’s districts. The samples were distributed in four stages, the first composed of all the coffees entered in the contest, and the last composed only of the pre-finalists. The samples were categorized into natural and CDs (pulped natural, demucilaged and demucilaged/pulped natural). The spatialization of the samples from both years was done using Kernel maps to visualize the intensity of sample concentrations in each stage of the contest. The results show that in the first stage the samples were well distributed, with medium, high and very high intensity focus. In the fourth stage, a high concentration in the Sul de Minas region was observed in both years for both coffee categories.